Handbook of flexible manufacturing systems - Jha, Nand K (Academic Press, 1991)
This handbook is a compilation of the current practical knowledge of flexible manufacturing systems (FMS). FMS allow manufacturing plants of all sizes to reduce their inventory while increasing their ability to meet consumer demands. By controlling automatic guided vehicles, robots, and machine tools with one central computer, products can now be produced in a variety of styles and models all at the same time. FMS are designed to adapt quickly and economically to changes in requirements and to unpredictable events. This guide explains how to effectively employ these useful new systems.